2017
DOI: 10.3390/risks5030049
|View full text |Cite
|
Sign up to set email alerts
|

Model Uncertainty in Operational Risk Modeling Due to Data Truncation: A Single Risk Case

Abstract: Abstract:Over the last decade, researchers, practitioners, and regulators have had intense debates about how to treat the data collection threshold in operational risk modeling. Several approaches have been employed to fit the loss severity distribution: the empirical approach, the "naive" approach, the shifted approach, and the truncated approach. Since each approach is based on a different set of assumptions, different probability models emerge. Thus, model uncertainty arises. The main objective of this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The construction of the relative efficiency curves (REC) is described in Appendix A.2. Note that more detailed presentations of parts of this material are available in Brazauskas (2009) and Yu and Brazauskas (2017).…”
Section: Appendix Amentioning
confidence: 99%
See 1 more Smart Citation
“…The construction of the relative efficiency curves (REC) is described in Appendix A.2. Note that more detailed presentations of parts of this material are available in Brazauskas (2009) and Yu and Brazauskas (2017).…”
Section: Appendix Amentioning
confidence: 99%
“…However, when all those models were used to estimate the 90% and 95% quantiles (value-at-risk measures) for ground-up loss, for some data sets they resulted in similar estimates, which would be expected, while for others they were far apart, which is counterintuitive. Moreover, using left-truncated operational risk data, Yu and Brazauskas (2017) have shown that even shifted parametric models (which might seem like a plausible option but nonetheless incorrectly account for data truncation) can pass those standard model validation tests. Next, due to the presence of deductibles and policy limits in insurance contracts, data truncation and censoring are unavoidable modifications of the loss severity variable.…”
Section: Introductionmentioning
confidence: 99%
“…Jha & Chakraborty [3] and Chaves Agudelo [4] respectively related to the distributional properties and continuity of the Lumax norm values. Yu and Brazauskas [5] referred to and submitted applications for this position in support of data resulting from inaccurate and incorrectly truncated Lomax distributions. Chakraborty [6].…”
Section: Introductionmentioning
confidence: 99%
“…Carolyn W. Chang and Jack S. K. Chang (Chang and Chang (2017)) utilize an approach that integrates commonly used tools from actuarial science and mathematical finance to price a default-risky catastrophe reinsurance contract. Daoping Yu and Vytaras Brazauskas (Yu and Brazauskas (2017)) study the impact of model uncertainty on value-at-risk (VaR) estimators. In her paper on predicting prices for high profile tech stocks, Nguyet Nguyen (Nguyen (2017)) applies the Hidden Markov Model (HMM) to forecast stock prices and develop an HMM-based trading strategy.…”
Section: Overviewmentioning
confidence: 99%